2006
DOI: 10.1111/j.1468-1331.2006.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Using translational medicine to understand clinical differences between botulinum toxin formulations

Abstract: When using botulinum toxin-based products, the physician must decide the optimal location and dose required to alleviate symptoms and improve the patient's quality of life. To deliver effective treatment, the physician needs to understand the importance of accurate target muscle selection and localization and the implications of each product's migration properties when diluted in different volumes. Pre-clinical mouse models of efficacy and safety have been utilized to compare local and distal muscle relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 46 publications
1
55
0
1
Order By: Relevance
“…A rough estimate is that 1 A/Ona U corresponds 1 U A/Inco, 3e5 A/Abo U, and 50 B/Rima U, but the equivalence changes under different conditions. The reported equivalence ratio A/Abo: A/Ona in clinical studies ranges widely (1:1e1:11), although the most commonly quoted figures are 1:3 or 1:4 (Sampaio et al, 1997;Aoki et al, 2006;Bentivoglio et al, 2012). In two randomized, controlled studies, A/ Abo produced better results than A/Ona at 1:4 ratio, with higher occurrence of side effects (Sampaio et al, 1997;Nüssgens and Roggenk€ amper, 1997).…”
Section: Comparing the Potency Of Different Bonts/a: Bioequivalence Omentioning
confidence: 98%
“…A rough estimate is that 1 A/Ona U corresponds 1 U A/Inco, 3e5 A/Abo U, and 50 B/Rima U, but the equivalence changes under different conditions. The reported equivalence ratio A/Abo: A/Ona in clinical studies ranges widely (1:1e1:11), although the most commonly quoted figures are 1:3 or 1:4 (Sampaio et al, 1997;Aoki et al, 2006;Bentivoglio et al, 2012). In two randomized, controlled studies, A/ Abo produced better results than A/Ona at 1:4 ratio, with higher occurrence of side effects (Sampaio et al, 1997;Nüssgens and Roggenk€ amper, 1997).…”
Section: Comparing the Potency Of Different Bonts/a: Bioequivalence Omentioning
confidence: 98%
“…It has been claimed that, because of the size of the complexes, the diffusion of neurotoxin into adjacent tissues is slower in the high molecular weight complex compared with the lower molecular weight complexes or with free neurotoxin. 2 This possibility has not been analyzed in vivo. Therefore, owing to its paramount importance, we undertook an ad hoc study to compare the diffusion of the above-mentioned BoNT/A formulations in vivo.…”
mentioning
confidence: 99%
“…In our paradigm we did not include patients with other type of dystonia (e.g. torticollis) since size and number of cholinergic synapses, density and type of muscular fibers, as well as the number and precise site of the injections, may be variable across subjects further increasing the variability of outcome after BoNT treatment [8]. Therefore, in order to avoid the differences related to intra-and inter-individual variability, we focused our interest only in patients receiving BoNT into orbicularis oculi, given also its anatomical consistency across subjects.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of attempts (in vivo and in vitro animal models, clinical evaluations in humans) have been made to find a conversion factor that would allow a reliable conversion between Botox Ò and Dysport Ò (Table 4). Published conversion factors ranged from 1:1 [9] to 1:11 [10], although the most commonly quoted figures are 1:3 or 1:4 [8]. Two randomized and controlled studies using a conversion factor of 4 showed that Dysport Ò is more likely to produce better results (considering both efficacy and duration of improvement) than Botox Ò but it is associated with an increased occurrence of side effects [11,12].…”
Section: Discussionmentioning
confidence: 99%